2021
DOI: 10.1098/rsos.201744
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis and characterization of silver-loaded graphene oxide nanomaterials and their antibacterial applications

Abstract: With the promising potential application of Ag/graphene-based nanomaterials in medicine and engineering materials, the large-scale production has attracted great interest of researchers on the basis of green synthesis. In this study, water-soluble silver/graphene oxide (Ag/GO) nanomaterials were synthesized under ultrasound-assisted conditions. The structural characteristics of Ag/GO were confirmed by Fourier transform infrared spectroscopy, X-ray diffraction, transmission electron microscopy, scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The lower particle size and the higher surface area of NPs/NCs are associated with increased biological activity. 46 , 47 Figure 3 D–F shows the high-resolution TEM images of ZnO NPs, Mo-ZnO NPs, and Mo-ZnO/RGO NCs, respectively. These pictures depict that particles were highly crystalline and confirm the synergism of ZnO, Mo, and RGO with good-quality lattice fringes without defects, which is important in composite materials for potential biomedical applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The lower particle size and the higher surface area of NPs/NCs are associated with increased biological activity. 46 , 47 Figure 3 D–F shows the high-resolution TEM images of ZnO NPs, Mo-ZnO NPs, and Mo-ZnO/RGO NCs, respectively. These pictures depict that particles were highly crystalline and confirm the synergism of ZnO, Mo, and RGO with good-quality lattice fringes without defects, which is important in composite materials for potential biomedical applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Decrements in the particle size of NPs after the incorporation of RGO were also reported in other studies [ 16 , 46 , 48 ]. Nanoscale materials with a smaller size and higher surface area exhibited higher biological activity [ 26 ]. High-resolution TEM images ( Figure 4 C,D) show the clear lattice fringes with measured interplanar distances of 0.233 and 0.229 nm for pure Ag NPs and Ag/RGO NCs, respectively, which corresponds to the (111) plane of the face-centred cubic structure of Ag [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanoscale materials with a smaller size and higher surface area exhibited higher biological activity [ 26 ]. High-resolution TEM images ( Figure 4 C,D) show the clear lattice fringes with measured interplanar distances of 0.233 and 0.229 nm for pure Ag NPs and Ag/RGO NCs, respectively, which corresponds to the (111) plane of the face-centred cubic structure of Ag [ 26 ]. Elemental analysis of Ag/RGO NCs by TEM-led EDS indicated the presence of Ag, C, and O elements with no impurities ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO film demonstrated acceptable adhesion to root dentin, a significant inhibition of the bacterial proliferation and biofilm formation. Water-soluble Ag/GO nanomaterials were synthesized by Zhu et al [ 46 ] under ultrasound-assisted conditions and characterized by FTIR, X-ray diffraction, TEM, and SEM/EDX. The results showed that the silver particles are strongly attached to the GO surface and that the Ag/GO composites could inhibit the growth of S. aureus .…”
Section: Antimicrobial Activity and Applications Of Graphene Nanomaterialsmentioning
confidence: 99%